The Influence of Celebrity Endorsers and Perceived Quality on Intention to Purchase Local Beauty Products: Mediation Analysis of Brand Loyalty and Moderation of Negative Publicity - Anisa Fera; Aflit Nuryulia Praswati (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research examines the influence of celebrity endorsers and perceived quality on the purchase intention of local beauty products, with brand loyalty as a mediator and negative publicity as a moderator. Using a quantitative approach with the Structural Equation Modeling-Partial Least Square (SEM-PLS) method, data from 180 respondents were analyzed. Convenience sampling, while practical, may limit generalizability due to potential bias. Future studies should consider more diverse sampling techniques. Findings indicate that celebrity endorsers significantly impact purchase intention and brand loyalty, with brand loyalty further enhancing purchase intention. Perceived quality indirectly influences purchase intention through brand loyalty. However, negative publicity does not significantly moderate the relationship between celebrity endorsers and purchase intention. This unexpected result suggests further exploration of the nature of negative publicity and potential moderating factors like product type or celebrity image. This study highlights brand loyalty’s critical role in purchasing behavior and offers insights for marketers on leveraging celebrity endorsers effectively. The findings contribute to marketing literature by reinforcing the strategic importance of brand loyalty and endorsement strategies. Future research should explore additional theoretical perspectives to strengthen understanding in consumer behavior and marketing.